Maternal factors of low birth weight babies in an antenatal care hospital in Bangladesh - Begum, Musammet Rasheda; Biswas, Soma Chowdhury (Asian Journal of Medical and Biological Research, 2020)
Low birth weight (LBW) has been considered as the strongest predictor of child morbidity and mortality. The goal of this study was to inspect the socio-demographics and nutritional status of mother and its impact on neonatal birth weight. A cross-sectional study was conducted among 85 mothers with third trimester’s pregnancy period of age between 17 to 35 years in maternal health care centers at Chittagong, Bangladesh. Average age of mothers was 24 04 years and age at marriage it was 18 03 years. Height and MUAC of the respondents were 153 5.37 cm and 25.53 3.09 cm respectively. Half of participants suffered from anemia (Hb level <11 g/dL). Average birth weight was 2759.7 561.42 g. The preterm birth was 10.6% and about 22.35% babies delivered by C section. Twenty eight percent of offspring were born with low birth weight (LBW), among the LBW babies, 11.76 % were born at home and 16.47 % at hospital. Maternal height (AOR: 2.79; 95% CI: 1.02-8.44), Mid Upper Arm Circumference (MUAC) (AOR 2.73; 95% CI 1.03-8.01) and gestational age (AOR 8.92, 95% CI: 1.76-45.16) were significantly associated with LBW of babies after adjusting the education level of mothers. The proportion of LBW was not negligible which still national public health concern in Bangladesh. Proper nutrition and monitoring on gestational length might minimize small size babies. Asian J. Med. Biol. Res. June 2019, 5(4): 271-279